2019
DOI: 10.1111/cas.13992
|View full text |Cite
|
Sign up to set email alerts
|

Nectin‐2 in ovarian cancer: How is it expressed and what might be its functional role?

Abstract: Nectin‐2 is an adhesion molecule that has been reported to play a role in tumor growth, metastasis and tumor angiogenesis. Herein, we investigated Nectin‐2 in ovarian cancer patients and in cell culture. Tumor as well as peritoneal biopsies of 60 ovarian cancer patients and 22 controls were dual stained for Nectin‐2 and CD 31 using immunohistochemistry. Gene expression of Nectin‐2 was quantified by real‐time PCR and differences analyzed in relation to various tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 36 publications
3
27
0
1
Order By: Relevance
“…Next, we performed PVRL2 fluorescent immunohistochemistry on benign/normal ( n = 5) and HGSOC ( n = 15) samples. Mean and maximum intensity was 1.6-fold and 2.4-fold greater, respectively, in HGSOC compared to normal/benign tissue ( p = 0.0021, p = <0.00001) ( Figures 5D–F ), which is in agreement with published studies ( 29 , 30 ).…”
Section: Resultssupporting
confidence: 92%
“…Next, we performed PVRL2 fluorescent immunohistochemistry on benign/normal ( n = 5) and HGSOC ( n = 15) samples. Mean and maximum intensity was 1.6-fold and 2.4-fold greater, respectively, in HGSOC compared to normal/benign tissue ( p = 0.0021, p = <0.00001) ( Figures 5D–F ), which is in agreement with published studies ( 29 , 30 ).…”
Section: Resultssupporting
confidence: 92%
“…DNAM-1 + GM NK-92 cells degranulated against all primary sarcoma explants as well as against the majority of the established cell lines, proving the potential of CD112 and CD155 as tumorspecific markers for targeted immunotherapies (Figures 3, 7). This, along with the absence of the degranulation response of NK cells against healthy donor PBMCs, showed that the use of DNAM-1 + GM NK-92 cells could be restricted/directed only to targets that had elevated CD112 and/or CD155 expression (Figures 2, 7), which is observed in tumors from various origins (65)(66)(67)(68)(69)(70)(71)(72)(73)(74)(75)(76)(77)(78)(79)(80)(81)(82)(83), including osteosarcomas (24).…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, a phase I/II study evaluating poliovirus receptor related immunoglobin domain containing (PVRIG) alone and in combination with nivolumab has been initiated for solid tumors, including ovarian cancer (NCT03667716). Intriguingly, it has been found that PVRIG’s ligand, poliovirus receptor related-2 (PVRL2) is substantially upregulated in EOC [ 108 , 109 ], indicating the potential efficacy of targeting PVRIG along with PD-1.…”
Section: Pd-1 Based Combinatorial Approachesmentioning
confidence: 99%